ANALISIS PENGARUH HARGA, KUALITAS PRODUK, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Pembeli Produk Bandeng Juwana Elrina Semarang) - Ghanimata, Fifyanita; Kamal, Mustafa (Faculty of Economics and Business Diponegoro University, 2012)
ABSTRACT This study aims to determine how big the influence of price, quality of product, and location of the purchase decision on the Bandeng Juwana Elrina Semarang. And this research also aims to analyze the most dominant factors that influence on purchase decisions on the Bandeng Juwana Elrina Semarang. The population used in this study is consumers who ever or frequently come on the Bandeng Juwana Elrina Semarang. The sample in this study are 80 respondents and the techniques used are non-probability sampling technique with the approach of accidental sampling (sampling based on chance). Analytical methods used were quantitative analysis of multiple regression analysis. This analysis includes: validity and reliability, the classic assumption test, multiple regression analysis, hypothesis testing by t test and F test, and analysis of determination coefficient (R2). The location variables have the most impact on purchasing decisions for 0,329, followed by quality ofÂ products variable amounting to 0,323. While the price variables have an influence lowest compared to other variables for 0,242. Hypothesis testing using t tests showing that the three independent variables are price (X1), quality of product (X2), and location (X3) which investigated proved positively and significantly affect the dependent variable is the purchase decision (Y). Then through the F test can be seen that the variables price, quality of product, and location eligible to test the dependent purchasing decisions. Adjusted R Square explained figures that 62,3% of purchase decisions variation can be explained by the three independent variables in multiple regression equations. While the rest of 37,7% was explained by other variables outside of the three variables used in this study.